What determines young adults' attitudes, perceived norms, and perceived behavioral control towards healthy sleep behaviors? A reasoned action approach - Paul Branscum; Katie Qualls Fay (New Prairie Press, 2019)
A common limitation to the design of public health sleep interventions is the overall lack of using theory. Previous researchers have utilized the theory of planned behavior and the reasoned action approach (RAA) to predict healthy sleep behaviors, however much of this research was done using reflective (or generalized) measures, which alone is likely inadequate to equip health practitioners with tangible information they can use to translate theory into practice. Therefore, the purpose of this study was to use formative (or belief-based) measures of the RAA to evaluate the determinants of attitudes, perceived norms, and perceived behavioral control (PBC) of healthy sleep behaviors among young adults.A survey was distributed via email using a university-wide listserv at a large southwestern university. Participants (n = 310) were on average 19.9 years old (+/-1.6), and reported sleeping five and a half hours (+/-0.7) per night. Associations between formative and reflective RAA measures were overall moderate to strong. Thinking clearly (r = 0.55; p < 0.001) was the strongest determinant of attitudes; friends (r = 0.27; p < 0.001) was the strongest referent of injunctive norms; children (r = 0.14; p < 0.05) was the strongest referent of descriptive norms; and having a lot of homework/studying (r = -0.25; p < 0.001) was the strongest determinant of PBC. Understanding the determinants of attitudes, perceived norms, and PBC will help health practitioners bridge the gap between theory and practice, and provide relevant information to aid in the development of effective public health sleep interventions.